Augustus и Σεβαστός: о семантике терминов - Токарев, А.Н. (My University, 2005)
A. Tokarev. Augustus and Σεβαστός: About Semantics of Terms In the article is examined the comparative characteristic of semantic meanings of augustus and Σεβαστός. In author’s opinion, there was evolution of meanings of word augustus, the specific term concerning sphere of religion. During the King’s epoch and the epoch of Republic meaning of this word was «glorified a deity», «majestic». However at the end of Republic augustus started to lose the sacral sense. Octavian, having accepted cognomen Augustus, has made an attempt to return original sense to this word. During the Augustan epoch poets and writers used augustus in his original meaning. However in the time of empire the tendency of easing of sacral meaning of augustus amplify to admirabilis and magnificus. At the same time there is a new tendency. Augustus becomes with time a epiklesis for gods. That is, on the one hand, this word means «surprising», «delightful», on the another — «sacred». Comparison of the use of words Σεβαστός and Αὔγουστος in the Greek sources and the fact of appearance of an adjective σεβαστός for the first time in the Greek language only after 27 BC show that Σεβαστός was official translation of a Latin name of the Roman emperors. It is evidence of a choice of Augustus’ Greek translation has been made with Latin analogue simultaneously, among an environment of the first Roman emperor and hardly was casual. The reason of a choice of such translation, probably, have been connected with the fact that in the Eastern Greek-speaking areas of the Roman Empire the government of August carried out a politics on sacralisation of emperor’s person meaningly.